UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA INTERAKTIF QUIZIZZ PAPER MODE SISWA KELAS VI SD NEGERI 064974 MEDAN TEMBUNG - Hasibuan, Salsabila; Muhammad Arifin; Harahap, Tetty Rosmaida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This classroom action research aims to improve the learning outcomes in Mathematics for sixth-grade students at SD Negeri 064974 Medan Tembung, using the interactive Quizizz paper mode method. This research type, known as classroom action research (PTK), employs a descriptive quantitative approach. This research was conducted at SD Negeri 064974 Medan Tembung. The subjects of this study were sixth-grade students, consisting of 27 students. The goal of this research is to examine the impact of learning. The research was conducted in two cycles and was carried out collaboratively between researchers and tutors. We used tests and observation sheets as data collection techniques. The results of this study indicate that the application of the Quizizz paper mode in learning, especially as an evaluation tool, can improve the learning outcomes of sixth-grade students at SD Negeri 064974 Medan Tembung. This increase is shown by the quality of the learning process, liveliness, enthusiasm, and enthusiasm, as well as test scores on student learning outcomes. The increase is evident in the average score of students' test results from pre-action to cycle II. The average student score in the pre-action was 63, increased in cycle I to 74, and then increased again in cycle 2 to 80. The percentage of completeness from cycles I and II was 66.67% (18 students), respectively, increasing in cycle II to 85.18% (23 students). This research is considered successful because it has met the completeness criteria, which requires 75% of students to receive scores greater than or equal to KKM (75).